Integration of STEM Technologies in Geography Education - Laiskhanov, Sakhislam; Seminar, Yerkegul; Amandyk, Kopbossyn (Indonesian Journal of Geography, 2026)
This study examines the integration of STEM technologies into geography programs in higher education institutions to develop students' research competencies, spatial thinking, and interdisciplinary problem-solving skills. Based on a systematic analysis of 29 recent publications on STEM in geography education, the study identifies five key features of STEM-based learning: organizing research activities, developing practical and analytical skills, encouraging innovative and project-based thinking, effectively using digital tools and GIS, and gradually introducing STEM methodologies. Drawing on the international experience of countries such as Malaysia, China, and Indonesia, a STEM laboratory model for teaching geography is proposed. The results show that the structured implementation of STEM technologies significantly improves students' ability to conduct experiments, analyze data, make predictions, and develop critical thinking, thereby preparing future specialists to solve social, environmental, and economic problems. This study lays the foundation for integrating STEM into geography curricula and offers practical recommendations for creating a laboratory learning environment in universities. In general, geography, using STEM technology, can study or analyze issues such as urbanization, socioeconomic inequality, disease incidence (mapping), migration, natural.